2012
DOI: 10.1159/000343754
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of High-Temperature Stress on Nuclear Topology and Transcription of Repetitive Noncoding and Coding Rye Sequences

Abstract: The plant stress response has been extensively characterized at the biochemical and physiological levels. However, knowledge concerning repetitive sequence genome fraction modulation during extreme temperature conditions is scarce. We studied high-temperature effects on subtelomeric repetitive sequences (pSc200) and 45S rDNA in rye seedlings submitted to 40°C during 4 h. Chromatin organization patterns were evaluated through fluorescent in situ hybridization and transcription levels were assessed using quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 92 publications
0
12
0
Order By: Relevance
“…As such, in this study, we observe a response of the genome structure and transcription to external stimuli, namely, the AraC drug treatment. Numerous studies have shown a link between relatively rapid alterations of the nuclear architecture as a response to external stimuli including (a) thalidomide-dependent alteration of chromatin supra-organization in drug-resistant myeloma cells [80]; (b) marked ribosomal DNA (rDNA) chromatin decondensation and a significant increase in ribosomal gene expression in rye cells subjected to high-temperature stress [81]; and (c) bursts of action potential in cultured hippocampal neurons that cause remodelling of the nucleus to obtain ‘unfoldings’ which are thought to improve the cellular response to calcium signalling [82]. A possible outcome of the overlapping responses in 3D organization and transcription could be increased cell adaptation to the changed environmental cues.…”
Section: Discussionmentioning
confidence: 99%
“…As such, in this study, we observe a response of the genome structure and transcription to external stimuli, namely, the AraC drug treatment. Numerous studies have shown a link between relatively rapid alterations of the nuclear architecture as a response to external stimuli including (a) thalidomide-dependent alteration of chromatin supra-organization in drug-resistant myeloma cells [80]; (b) marked ribosomal DNA (rDNA) chromatin decondensation and a significant increase in ribosomal gene expression in rye cells subjected to high-temperature stress [81]; and (c) bursts of action potential in cultured hippocampal neurons that cause remodelling of the nucleus to obtain ‘unfoldings’ which are thought to improve the cellular response to calcium signalling [82]. A possible outcome of the overlapping responses in 3D organization and transcription could be increased cell adaptation to the changed environmental cues.…”
Section: Discussionmentioning
confidence: 99%
“…Portuguese Avena species diversity evaluation was also studied through the analysis of other repetitive sequences previously assessed in cereals, such as pSc200 sequence—a major family of sequences isolated from rye and mapped in subtelomeric domains [ 32 , 45 ]. In this work we amplified in Avena a 444 bp fragment with primers previously used in rye and wheat lines with rye chromatin introgression [ 31 ] and sequence analysis revealed a high level of similarity (99%–100%) with rye original pSc200 sequence (Accession Number Z50039) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…FISH analysis was performed as previously described [42]. The Athila4-6 IRAP amplified from "Fava Do Algarve" (5357) labeled with biotin-dUTP (Roche, Basel, Switzerland) was used as probe.…”
Section: Fluorescence In Situ Hybridization (Fish)mentioning
confidence: 99%